KOMUNIKASI INTERPERSONAL ORANG TUA TERHADAP ANAK DALAM MENCEGAH PERNIKAHAN DINI DI DUSUN III SINDAR PADANG - Ayu Wardani; Achiriah Achiriah; Syahrul Abidin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is entitled "Interpersonal Communication of Parents to Children in Preventing Early Marriage". The purpose of this study is to explain how parent-child interpersonal communication prevents early marriage in Hamlet III Sindar Padang. The research method used in this study uses qualitative research with a descriptive approach and data collection techniques through interviews and documentation, then the data is selected from the words that have been collected, analyzed interrelated to obtain temporary conjectures and draw conclusions from these results. The results of this study indicate that the interpersonal communication carried out by parents towards their children has been going quite well, the communication carried out by parents uses verbal and non-verbal means and parents communicate quite often with children. When communicating, parents use kind words, there is no coercion, provide understanding and attention and get closer to children like friends so that children are more open and comfortable when communicating with parents. Although in the end the parents allowed their children to marry at a young age because of their own wishes. Still, parents still direct their children, that is, parents always communicate with their children, always give advice and give understanding to their children.